Effect of dividend on stock price: an Indian perspective / Shilpa Jain and Vijay Kumar Gupta - Jain, Shilpa; Gupta, Vijay Kumar (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2020)
This paper aims to find out the effect of dividend on share price in India. For this purpose, the researchers collected data from a sample of 50 firms of the NIFTY-50 index from 2008-2018. Independent variables were dividend per share and retention ratio. Control variables were return on equity, profit after tax, and earnings per share. Panel regression methods like the pooled OLS regression, fixed-effect model, and random effect model were applied. The results supported the fixed-effect model. The findings confirm the hypotheses that dividend per share and retention ratio have no significant impact on share price, which further affirms Miller and Modigliani’s theory stating that share prices are unaffected by dividend payments by a firm. However, the result shows that earnings per share and return on equity have a significant impact on share price, attributing to the viewpoint that companies which are effective in utilizing capital invested by shareholders and make a profit for them are valued high.